Effects of growth temperatures on the structural and optoelectronic properties of sputtered zinc sulfide thin films for solar cell applications - Haque F.; Rahman K.S.; Islam M.A.; Yusoff Y.; Khan N.A.; Nasser A.A.; Amin N. (Springer New York LLC, 2023)
Buffer layers; Growth temperature; II-VI semiconductors; Sputtering; Sulfur compounds; Thin film solar cells; X ray diffraction; Zinc sulfide; Electrical characteristic; Film characterizations; Hall effect measurement; Optoelectronic properties; Preferential orientation; Solar-cell applications; Substrate temperature; Zinc sulfide thin films; Thin films